SOCIETIES RESILIENCE FOR CONFRONTING COVID-19 BASED ON GOTONG ROYONG TRADITION (MUTUAL COOPERATION) - Bahagia Bahagia; Rahmadanti Rahmadanti; Indriya Indriya (Tunas Geografi, 2020)
The research investigates about Societies resilience for facing COVID 19 based on mutual cooperation. The studies used is ethnography qualitative approach. The method is selected because of research linked to tradition and cultural, societies, and community. Data are collected by in-depth interview, observation and documentation. Purposive sampling technique is implied to determine respondents as major sources information. The outcome is analyzed with triangulation data. The result is mutual cooperation tradition have been implemented in some activity including mutual helping and mutual cooperation in public activity and mutual helping when there is societies suffer from the ailment. It can create societies resilience because there is social power to bolster individual resilience by way of mutual helping and visiting when the member of societies suffer from the disease. In addition, mutual cooperation has invented food resilience because of societies collectively bringing food to people who they are combated by a disease like COVID 19. At the same time, people who suffer from a disease like COVID 19 can achieve physiology resilience. A person who they have been encouraged by the societies collectively easier to recover from the ailment because the person doesn’t experience stress for confronting disturbance of life. As result, the person has happiness and produce happy hormones rather than sad hormone. Directly, the rate of spirit for healing attaint through mutual cooperation. Another finding is societies have moved from traditional social relation to online relation without face to face. The impact is societies react resilience because they avoid from COVID 19 attack through reducing face-face meeting frequency. Even societies literate about update information related to COVID and simple societies to literate about online and social media. It boosts resilience societies because a person has information about COVID 19.